Distribution of responsibility for social security and labour market policy. Country report: Denmark - Madsen, Per Kongshøj (Amsterdam, 2007)
"High levels of unemployment, or high levels of social expenditures as well as the growing demand for a flexible labour force have given new impetus to the world-wide discussion on what model to use for an efficiently operating labour market and in particular on the role of institutions. Although there seems to be a growing consensus on the restricted governmental role in recent decades, this has not been translated into a unanimous appraisal of the role of intermediary organisations, such as trade unions. There is no clear view on an appropriate distribution of responsibility between government, social partners and the market. The research project ‘distribution of responsibility for social security’ aims to create a scientific basis for a clear and consistent view on the role and distribution of responsibilities between the different labour market institutions. As part of this research project, this paper provides an elaborate country study of Denmark."